Quality of refrigerated raw milk according to the bulk transport conditions - Felipus N.C.* (2023)
© 2023, Eduem - Editora da Universidade Estadual de Maringa. All rights reserved.Technical regulations that determine milk quality standards in Brazil establish the minimum criteria that the processing industry's raw material must present. These rules can challenge the logistics sector (transport) to maintain adequate milk conservation levels. We aimed to evaluate the influence of bulk transport and storage conditions on refrigerated raw milk quality. The experiment was carried out in a dairy industry in Santa Catarina State. Information and samples of refrigerated raw milk were collected from dairy farms, from isothermal compartments of milk trucks, and from the industry's storage silo. These samples were submitted to microbiological analysis, somatic cell count (SCC), and physicochemical analysis. The results were evaluated by ANOVA and multivariate analysis (factor analysis). The transport of raw milk in bulk and the transfer of raw material to the industrial silo worsened the milk's microbiological quality (p < 0.0001) for standard plate count (SPC) and psychrotrophic microorganism count (PMC), without affecting, the physicochemical characteristics of the milk (p > 0.05). Poor hygienic conditions in milk storage rooms, in the refrigeration bulk tanks of the dairy farms, and during the transport, as well as the transport on longer routes, were related to higher SPC and psychrotrophic count while receiving milk by the dairy industry with higher temperatures was only associated with higher SPC.